Benjamin Joseph Ingram Photograph of Health Care Employees - Ingram, Benjamin Joseph::::::::: (2021)
Photograph posted to social media of Benjamin Joseph Ingram with colleagues wearing personal protective equipment while working at a dialysis clinic. The contributor writes, "I work as an EMT in Alameda County. This photo was taken on April 30th 2020, outside of a dialysis clinic in Milpitas that is currently only serving COVID positive patients. At the time this photo was taken, well documented was the national shortage of PPE, the fatigue of healthcare workers, and civic unrest. This was our third COVID positive patient of our 10 hour shift, and I was feeling the burnout that so many healthcare workers are experiencing. I was on my 45th pair of gloves of the day (not an exaggeration), and my nose was chafed and splitting open under my N-95 mask from days of extended use. As we were getting ready to pick-up our patient, my partner (on the right of the photo) asked me to take a photo of her in her new, very fashionable, face mask in addition to one of the two of us together. "As we were taking the photo of us, one of my favorite dialysis technicians recognized me and took the opportunity to surprise us from behind and jump in the photo. My partner would later go on to post the photo to her Instagram account. The photo at the time didn't mean much to me as I was fatigued, but it has come to represent much more in the days since. It represents how strong the human spirit can be and how even in the midst of an oddly dystopian aura that has come with the pandemic and that we are able to take a moment to have some fun and share a smile and moment together which has been too far in between as of late. "I have since remembered the magnitude of what we do as EMT's on a daily basis. We don't have the choice of working from home and we certainly do not have the choice to not show up for our patients, regardless of circumstance. Even if I have to split my nose open and lose ten pound in sweat under my PPE, our patients still need to receive treatment. I am so fortunate to be working, and caring for those who need it the most. I am reminded that no matter how long this pandemic lasts, my love for caring for others will undoubtedly outlast it."